Penerapan Pidana terhadap Korporasi sebagai Pelaku Kejahatan dalam Perlindungan Kesehatan dan Keselamatan Kerja (K3) Buruh di Indonesia - Parningotan Malau (JURNAL MERCATORIA, 2020)
Corporate crime in protecting K3 workers/laborers in the workplace is very structured. The corporation is always profit-oriented as much as possible without regard to social aspects. This situation makes it easy for corporations to disobey the applicable laws and regulations. This study aims to determine the application of criminal offenses for corporate offenders if negligent in providing protection of health, work safety for workers. The research method used in this study is normative research. The analysis technique used is qualitative analysis with the support of secondary data in the form of a Law document. The results showed that the application of criminal acts against corporate perpetrators who violated the Manpower Act in particular OHS was not optimal and was not yet effective. This finding is proven by the absence of protection from work accident cases because the Occupational Health Safety Act (OHS Law) is still dysfunctional and cannot be enforced (dysfunctional and non-enforceable). In connection with that, all cases of work accident cases do not use OHS Law as the basis for the indictment, the basis for prosecution, or the basis for a criminal prosecution, but instead, use the articles in KUHP and other special laws outside the unusual KUHP